Synthesis of pyrimidines by Fe3O4@SiO2-L-proline nanoparticles - Safaei-Ghomi Javad; Samadi Zahra (Main Group Metal Chemistry, 2020)
Fe3O4@SiO2-L-proline nanoparticles have been used as an effective catalyst for the preparation of pyrimidines by three-component reactions of 1,3-dimethylbarbituric acid, aromatic aldehydes and 4-methyl aniline or 4-methoxy aniline under reflux condition in ethanol. Fe3O4@SiO2-L-proline nanoparticles have been characterized by scanning electronic microscopy (SEM), powder X-ray diffraction (XRD), vibrating sample magnetometer (VSM), thermal gravimetric analysis (TGA), energy dispersive X-ray (EDS), dynamic light scattering (DLS) and FT-IR spectroscopy. This method provides several advantages including, the reusability of the catalyst, low catalyst loading, atom economy, short reaction times and high yields of products.